2021
DOI: 10.1007/s10597-020-00767-5
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behavior and Treatment Barriers in Anxiety Disorders: Results from a Representative German Community Survey

Abstract: Although effective therapies exist, treatment rates of anxiety disorders (AD) are low, raising the question why affected individuals do not receive treatment. We provide data from the nationally representative German Health Interview and Examination Survey-2011 (DEGS1) on the help-seeking behavior and perceived treatment barriers of 650 subjects with Diagnostic and Statistical Manual of Mental Disorders’ (DSM-IV AD). Only 26% of all cases with AD in the community reported having had contact with mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…The similar low help-seeking situation was also reported in other psychiatric disorders, such as anxiety. Over 40% of participants never considered seeking help for their anxiety problems in the German community residents ( 63 ). While in the schizophrenia population, the rate was higher, 63.8% of them sought medical help in Ethiopia ( 64 ) and 64.6% in China ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The similar low help-seeking situation was also reported in other psychiatric disorders, such as anxiety. Over 40% of participants never considered seeking help for their anxiety problems in the German community residents ( 63 ). While in the schizophrenia population, the rate was higher, 63.8% of them sought medical help in Ethiopia ( 64 ) and 64.6% in China ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our study appear to bear this out. Wang et al found a clear, the demands for psychological knowledge and interventions during COVID-19 epidemic in students with anxiety and depression symptom was significantly higher than those without (48). This may be due to college students with higher mental health literacy may better understand the contributing factors or the triggers of psychological problems, thus having less psychological distress (49).…”
Section: Discussionmentioning
confidence: 99%
“…49 The observation that patients with neurotic illnesses had an unusually large number of comorbid diagnoses indicate that they might have erroneously recognized their somatic symptoms as physical problems. [50][51][52] Some of the comorbid diagnoses might actually be misdiagnosed and contribute to treatment delays or inefficient use of healthcare resources. Underrepresentation of serious conditions like hypertension, metabolic and neoplastic diseases gave weight to this interpretation.…”
Section: Discussionmentioning
confidence: 99%